Facial expressions of emotion What lies beyond minimal universality? [article]. - Russell, James A.
This article discusses the controversy over whether attribution (recognition) of emotions from facial expressions is universal (P. Ekman, 1994; C. E. Izard, 1994; J. A. Russell, 1994). Agreement emerged on various issues. There exists at least Minimal Universality (people everywhere can infer something about others from their facial behavior). Anger, sadness, and other semantic categories for emotion are not pancultural and are not the precise messages conveyed by facial expressions. Emotions can occur without facial expressions, and facial expressions can occur without emotions. Further evidence is needed to determine the relationship between emotion and facial behavior, what determines that relationship, how facial behavior is interpreted, and how much the interpretation varies with culture and language. Ekman's (1994) objections are answered. -- (from the author)